2021
DOI: 10.1186/s12872-021-02175-3
|View full text |Cite
|
Sign up to set email alerts
|

Mid-term (up to 12 years) clinical and echocardiographic outcomes of percutaneous transvenous mitral commissurotomy in patients with rheumatic mitral stenosis

Abstract: Background Rheumatic heart disease (RHD) is still a concerning issue in developing countries. Among delayed RHD presentations, rheumatic mitral valve stenosis (MS) remains a prevalent finding. Percutaneous transvenous mitral commissurotomy (PTMC) is the intervention of choice for severe mitral stenosis (MS). We aimed to assess the mid-term outcome of PTMC in patients with immediate success. Methods In this retrospective cohort study, out of 220 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
2
6
0
Order By: Relevance
“…Of 482 patients who underwent PBMV in an Italian center between 1991 and 2010, only 11% had MR severity greater than mild (26). In this and another study, pre-PBMV MR severity was not identified as a predictor for long-term cardiac death, mitral surgery or repeat PBMV (26,28). PBMV was reported to be feasible in rheumatic MS with moderate or severe MR in a small single-center Chinese cohort (21).…”
Section: Pbmv In Moderate Mrmentioning
confidence: 65%
“…Of 482 patients who underwent PBMV in an Italian center between 1991 and 2010, only 11% had MR severity greater than mild (26). In this and another study, pre-PBMV MR severity was not identified as a predictor for long-term cardiac death, mitral surgery or repeat PBMV (26,28). PBMV was reported to be feasible in rheumatic MS with moderate or severe MR in a small single-center Chinese cohort (21).…”
Section: Pbmv In Moderate Mrmentioning
confidence: 65%
“…The quality of the procedural result has been widely described as a major predictor of long-term event-free survival [5,8]. A myriad of other factors has been reported as independently influencing either immediate or long-term results including among others: age; sex; atrial fibrillation; New York Heart Association (NYHA) class; previous surgical commissurotomy; valve calcification; concomitant mitral regurgitation (MR); MV gradient; and pulmonary arterial pressure [6][7][8][9][12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Mitral valve stenosis (MS), as a progressive disease, is one of the most important valvular disorders in developing countries, which can lead to significant morbidity and negative clinical outcomes (1). Rheumatic heart disease, as well as degenerative calcification of the mitral annulus, can be considered as major reasons for occurrence of MS (2).…”
Section: Introductionmentioning
confidence: 99%